2021
DOI: 10.1016/j.jsurg.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Redeployment of Surgical Trainees to Intensive Care During the COVID-19 Pandemic: Evaluation of the Impact on Training and Wellbeing

Abstract: OBJECTIVE The aim of this study was to evaluate the impact of redeployment of surgical trainees to intensive care units (ICUs) during the COVID-19 pandemic–in terms of transferrable technical and nontechnical skills and wellbeing. DESIGN This was a survey study consisting of a 23-point questionnaire. SETTING The study involved surgical trainees that had been redeployed to the (ICU) across all hospitals in London during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…From the eleven research studies included in the review, sample sizes ranged from ten (Marks, Edwards, & Jerge, 2020) to 1269 (Camilleri et al, 2020). One study reported 59% (N=19) of participants were male, and 41% (N=13) female (Payne, Rahman, Bullingham, Vamadeva, & Alfa-Wali, 2020). Other participant demographic characteristics such as ethnicity were not provided.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the eleven research studies included in the review, sample sizes ranged from ten (Marks, Edwards, & Jerge, 2020) to 1269 (Camilleri et al, 2020). One study reported 59% (N=19) of participants were male, and 41% (N=13) female (Payne, Rahman, Bullingham, Vamadeva, & Alfa-Wali, 2020). Other participant demographic characteristics such as ethnicity were not provided.…”
Section: Resultsmentioning
confidence: 99%
“…These included prone and positioning, maintaining vascular catheters and dialysis circuits, sedation, and administering vasoactive medication (Camilleri et al, 2020; Doussot et al, 2020; NHS England & NHS Improvement, 2020b). Redeployed staff was also often asked to liaise with families and required training on communicating bad news (Payne et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review of surgical trainees redeployed to critical care, 53 per cent reported feeling that redeployment had had a negative impact on their mental health. 19 The feelings of inadequacy associated both with the roles that ENT trainees were being asked to fulfil and with leaving their established teams potentially compounded an already stressful situation. It is possible that better use of their existing skill sets would have helped to reduce this emotional impact.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia providers can help with airway management, ventilation, and catheter access. Surgical teams can assist with procedures such as tracheotomy and thoracic tube insertion [ 64 ]. Perioperative nurses and operating room assistants can help with prone positioning and other forms of patient mobilization [ 21 ].…”
Section: Staff Allocation and Planning Strategies For Surge Capacitymentioning
confidence: 99%